2020
DOI: 10.3390/ijerph17165900
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of Grape Stalks by Fungi: Effect on Bioactive Compounds, Fiber Composition, Saccharification Kinetics and Monosaccharides Ratio

Abstract: Grape stalks, an inedible lignocellulosic residue from winemaking and agro-industrial grape juice production, can be valorized as a source of bioactive compounds and as feedstock for the saccharification and bioconversion of soluble sugars. Solid-state fermentation (SSF) by six white-rot fungi was applied as pretreatment. Fiber composition, free radical scavenging activity, four ligninolytic, and three hydrolytic enzyme activities were determined. Saccharification kinetics, yield, and productivity were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…In general, xylanase was a dominant fungal enzyme, being about three to eight times higher than the CMCase activity in all fungal strains except I. lacteus. Large differences within enzymatic activities detected in pretreated lignocellulosic substrates have been previously observed in several fungi, including all strains of this work [5,17,18,23]. As previously pointed out [36], this highlights the need to interpret the pattern of enzymatic activities detected as a function of interactions among fungal strains, substrates type and incubation periods.…”
Section: Fungal Pretreatment Of Chestnut Shells: Oxidative and Hydrol...supporting
confidence: 72%
See 1 more Smart Citation
“…In general, xylanase was a dominant fungal enzyme, being about three to eight times higher than the CMCase activity in all fungal strains except I. lacteus. Large differences within enzymatic activities detected in pretreated lignocellulosic substrates have been previously observed in several fungi, including all strains of this work [5,17,18,23]. As previously pointed out [36], this highlights the need to interpret the pattern of enzymatic activities detected as a function of interactions among fungal strains, substrates type and incubation periods.…”
Section: Fungal Pretreatment Of Chestnut Shells: Oxidative and Hydrol...supporting
confidence: 72%
“…WRF mediated degradation of recalcitrant lignin of plant cell walls, involves oxidation reactions catalyzed by laccase, LiP, MnP and VP enzymes. This group of enzymes, highly versatile in nature, are considered key factors in biomass pretreatment [5,[12][13][14][15][16][17][18][19]. Extracellular ligninolytic activities detected in WRF-fermented CNS are shown in Figure 1.…”
Section: Fungal Pretreatment Of Chestnut Shells: Oxidative and Hydrol...mentioning
confidence: 99%
“…It is estimated that thermal water softens up the rigid structure of CNS. Various studies have reported that hot water pretreatment at high pressure and high temperature can enhance enzymatic hydrolysis of biomass without the addition of other chemicals [ 14 , 28 ]. The released glucose concentrations were found to be 8.7 g/L, 12.0 g/L and 15.3 g/L at KOH concentration of 1%, 2% and 3%, respectively, and were not significantly affected by KOH concentrations above 3%.…”
Section: Resultsmentioning
confidence: 99%
“…Pretreatment of biomass is a key process required to improve the recovery of fermentable sugars in enzymatic hydrolysis [ 13 ]. Various pretreatment (physical, chemical and biological) of lignocellulosic biomass have been conducted to remove the lignin, which inhibits the enzymatic hydrolysis, and to enhance the depolymerization and dissociation of fermentable sugar [ 14 ]. Chemical pretreatment has been widely used because of its advantages of low process cost and high sugar recovery [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The generated by-products have been estimated to be around 25−30 kg/hL of produced wine, and on average, 4 kg of grape stalks are generated per each hL of produced wine, representing 10–15% of the total produced wastes [ 3 , 4 ]. Currently, grape stalks have been used as fertilizers, but most of the time they are disposed to landfills which, when not attended correctly, can cause environmental problems [ 5 , 6 ]. The nutritional content of grape stalks may not be appealing, limiting its use as a raw material for animal feeding, as they constitute a lignocellulosic fiber material composed mainly of cellulose (30–38%), hemicelluloses (14–21%), and lignin (17–33%) [ 4 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%